Enhancing STEM Education in Early Childhood: Science Process Skills, Effective Questioning, and Science Concept Understanding of Kindergarten Teachers in Greater Bandung Area - Meidina Rizkita; Lintang Ratri Prastika; Apriyagung Apriyagung; Zuhe Safitra; Reza Setiawan (Unnes Science Education Journal, 2026)
Aligned with Indonesia’s Education Roadmap 2025–2045 in improving Early Childhood Education (ECE) and promoting STEM learning in ECE to develop innovation and problem-solving skills in children from an early age, his study aims to examines the readiness of early childhood educators in the Greater Bandung area to implement STEM learning, focusing on three areas: science process skills (SPS), effective questioning, and science concept understanding. Utilizing a convergent parallel mixed-method design, data were collected from 17 purposively selected kindergartens through direct classroom observations, video and audio transcripts, and teacher interviews. The results show that kindergarten teachers in the Greater Bandung area demonstrate a "partial readiness" for STEM learning implementation. The result showed 58% teachers have incorporated four different SPS, particularly observation and experimenting, while skills such as classifying and measuring are less developed. Questioning practices were largely limited to basic strategies, with higher-order questions and peer collaboration rarely observed. In addition, the presence of misconceptions and the lack of scientific explanations indicate gaps in teachers’ science content knowledge. These findings point to the need for targeted professional development to strengthen early childhood educators’ skills and confidence in delivering STEM learning in ECE settings.